DBS: Journey to integrated reporting - HWANG, Soo Chiat (Institutional Knowledge at Singapore Management University, 2015)
In 2011, Mikkel Larsen, Managing Director, Head of Tax & Accounting Policy, Group Finance at DBS Bank had first mooted the idea of DBS adopting an integrated reporting approach, as he was convinced that this was a more holistic way of reporting on the bank’s business strategy and activities, linking each one of them clearly to the financial and non-financial impact it would have on its stakeholders. Once he had senior management buy-in, an internal committee was formed to embrace the integrated report (IR) and decide on the key questions of what to report, and how to report it. The result of this effort was the 2012 annual report. In 2012, when DBS adopted the integrated reporting approach, it was the first listed company in Southeast Asia to do so. The report had been well-received and garnered considerable attention from the external parties such as research analysts and the media. Based on feedback from DBS’s stakeholders, DBS incorporated changes that would make the 2013 IR more user-friendly and meaningful for its stakeholders. Larsen was, in May 2014, looking over the 2013 report, recognising that there was always room for improvement. For instance, in preparation for the following years’ annual reports, further enhancements, could include defining ‘materiality’, increasing stakeholder outreach, and reporting ‘outcomes’ as compared to ‘outputs’.